Comparing measures of decline to dementia in amnestic MCI subjects in the National Alzheimer's Coordinating Center (NACC) Uniform Data Set - Monsell, Sarah E.; Liu, Danping; Weintraub, Sandra; Kukull, Walter A. (International psychogeriatrics, 2012)
Background: Many studies have investigated factors associated with the rate of decline and evolution from mild cognitive impairment (MCI) to Alzheimer's disease (AD) dementia in elderly patients. In this analysis, we compared the rates of decline to dementia estimated from three common global measures of cognition: Mini-Mental State Examination (MMSE) score, Clinical Dementia Rating sum of boxes (CDR-SB) score, and a neuropsychological tests composite score (CS). Methods: A total of 2,899 subjects in the National Alzheimer's Coordinating Center Uniform Data Set aged 65+ years diagnosed with amnestic mild cognitive impairment (aMCI) were included in this analysis. Population-averaged decline to dementia rates was estimated and compared for standardized MMSE, CDR-SB, and CS using Generalized Estimating Equations (GEE). Associations between rate of decline and several potential correlates of decline were also calculated and compared across measures. Results: The CDR-SB had the steepest estimated slope, with a decline of 0.49 standard deviations (SD) per year, followed by the MMSE with 0.22 SD per year, and finally the CS with 0.07 SD per year. The rate of decline of the three measures differed significantly in a global test for differences (p < 0.0001). Age at visit, body mass index (BMI) at visit, Apolipoprotein E (APOE) ɛ4 allele status, and race (black vs. white) had significantly different relationships with rate of decline in a global test for difference among the three measures. Conclusions: These results suggest that both the rate of decline and the effects of AD risk factors on decline to dementia can vary depending on the evaluative measure used.